Analysis of the Dynamics of Structural Processes in the Context of Ensuring Sustainable Development - Simkiv, Lilia; Shults, Svitlana; Lutskiv, Olena; Andrusiv, Uliana (European Journal of Sustainable Development, 2021)
The tendencies and the extent of structural changes in the economy of the regions of Ukraine in the context of ensuring its sustainable development are examined in the context of the types of economic activity in terms of gross value added (GVA) during 2011-2018. In particular, the rate of change in the share of the structural mass of the economy of the regions that occurred during this period is estimated; the dynamic processes that took place in the structure of the economy of Ukrainian regions are analyzed. The analysis of the mass of structural changes shows their insignificant scale and reduction of the share in the structure of gross value added of such types of economic activity as industry, construction and finance. The estimation of intensity of structural changes by an indicator of average rates of their change shows low and rather differentiated level of intensity of structural changes in the context of types of economic activity. During the analyzed period, the annual average rate of structural changes in Ukraine was 0.131. Based on the calculation of the rate of structural changes, it is proved that structural changes in the economy of Ukraine are quite slow and are characterized by significant interregional differentiation, and the lack of positive dynamics in increasing the speed of structural changes in education is the main obstacle to creating an innovation-oriented model of economic development and reorientation of the structure of the regional economy to the requirements of the post-industrial type to the established concepts and dominants of sustainable development in accordance with EU standards.